Małgorzata Stefanowicz, „Polityka etniczna Litwy w latach 1990-2004”: Ośrodek Myśli Politycznej, Kraków 2019, ss 272 (Politeja, 2020)
Paradoxically, the issue of the policy of the Lithuanian state towards national minorities – arousing interest and emotions in Poland due to the Polish community there – has not yet been studied separately in Polish science. This gap is filled by the work of Małgorzata Stefanowicz Ph.D. ‘The ethnic policy of Lithuania in 1990–2004’. As a time framework, the author adopted the period from Lithuania’s independence until joining the European Union. The years 1988–1990 were also discussed in detail, that is the period of Sąjūdis’ activity. Actions taken then influenced inter-ethnic relations in later times. The analysis carried out in the work shows that the program drawn up at the dawn of independence was later modified. An important issue is the language, which for the creators of independence was more than just a communication tool. Małgorzata Stefanowicz’s work is a valuable contribution to the development of Polish research on contemporary Lithuania.